SPATIAL ANALYSIS OF LANDSLIDE POTENTIAL ON AGRICULTURE IN THE AYUNG WATERSHED, BALI PROVINCE - Feronika, Feronika; Osawa, Takahiro; Merit, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 2 (2023)DO - 10.24843/EJES.2023.v17.i02.p06, 2023)
The Ayung Watershed is one of the watersheds with mountainous and hilly landscapes with potential landslides. This study aims to determine the potential level of landslide susceptibility and its effect on agricultural land use in the Ayung watershed. The method used to determine the potential for landslides is a weighting/scoring method by overlapping the parameters causing landslides, namely rainfall, slope, land use, landform, geological structure, and soil type. Determining the effect of landslide potential on agricultural land is done by overlapping the landslide potential map with land use. The data used includes BMKG monthly rainfall for 2015-2019, the slope of DEMNAS data for 2020, geological structure and landform 1:25,000 scale RBI map data for 2019, land use using Sentinel 2A data for 2020, and soil types in the form of spatial planning maps Province of Bali 1:25,000 scale in 2019. The results showed that landslides in the Ayung watershed were categorized as low potential to high potential. Classes with no landslide potential are widespread in the upstream and downstream areas of the watershed, covering an area of ??18,976.01 ha (60%), the low potential category covering 5,877.78 ha (19%), the medium potential category covering an area of ??3,208.76 ha (10%) and the low potential category covering an area of ??3,208.76 ha (10%) spread over the upstream and central parts of the watershed covering an area of ??3,528.55 ha (11%). The effect of landslides on agricultural land has a category from no potential to high potential. The category with no potential is widespread in the upstream watershed area of ??13,268.57 ha (66%), the low potential category is 3,268.57 ha (16%), the medium potential category is 1,782.31 ha (9%), and the high category is spread in the upstream and the middle of the watershed area of ??1,707.28 ha (9%). Keywords : Landslide; Watershed; Mapping; Agricultural land